A novel method for continuous formation of cord‐like collagen gels to fabricate durable fibers in which collagen fibrils are longitudinally aligned. Issue 4 (10th September 2018) - Yunoki, Shunji; Hatayama, Hirosuke; Ebisawa, Mizue; Kondo, Eiji; Yasuda, Kazunori
Abstract: We developed a continuous formation method of cord‐like collagen gels comprising fibrils preferentially aligned along the geometrical axes (CCGs). Collagen (2.5%) dissolved in a sodium phosphate buffer containing 280 m M of sodium chloride was introduced into a stainless cylinder (length 52 mm, diameter 2.0 mm) warmed at 38°C at a linear velocity of 2.5 mm/s. This process caused collagen fibril alignments under acute fibril formation in the cylinder, resulting in continuous formation of CCGs. Fibril formation rate, shear rate, and shear duration were substantial factors for successful CCG formation. Outstanding advantages of this method over conventional wet spinning include the capacity of this technique to form aligned fibrils in the entire gels and to control the diameter of cord‐like gels over 1 mm. The air‐drying of CCGs which were crosslinked with 1‐ethyl‐3‐(3‐dimethylaminopropyl)‐carbodiimide and N‐hydroxy‐succinimide produced dry collagen fibers with cross‐sectional areas of 0.0123–0.135 mm 2 . Upon the rewetting of the fibers, they failed at a stress of 54.5 ± 7.8 MPa, which is higher than the mean failure stress of anterior cruciate ligament tissue (13.3–37.8 MPa). These findings indicate that the CCG formation method enables the fabrication of collagen fibers which are potential components of collagen‐based artificial tendons. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 1011–1023, 2019.